1998
DOI: 10.1097/00005537-199806000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Laryngeal Chemoreflex Severity With Laryngeal Muscle Response

Abstract: Objectives: To examine the relationship between the severity of the laryngeal chemoreflex (LCR) and the pattern of laryngeal muscle activity during an LCR‐induced apnea. Methods: The laryngeal mucosa of 20 piglets aged 17 to 20 days was stimulated under both hypoxic and normoxic conditions. Respiration, blood pressure, and activity of the thyroarytenoid (TA) and posterior cricoarytenoid (PCA) muscles were monitored during the LCR‐induced apnea. Results: Hypoxemia resulted in a shorter average apnea duration bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…However, profound or fatal apneas are more common under hypoxic conditions. 18 The results of the present study show that laryngeal stimulation during hypoxia (Pa02 of 50 to 65 mm Hg) results in a decrease in mean apnea duration and that a higher level of oxygénation before laryngeal stimulation results in a higher Pa02 level at the end of the apneic response. Despite this effect on apnea duration and recovery Pa02 level, hypoxia as defined in this study (mean prestimulation Pa02 level of 58.5 versus 82.5 mm Hg) did not affect the ability to recover from the apneic response without assistance.…”
Section: Discussionsupporting
confidence: 50%
“…However, profound or fatal apneas are more common under hypoxic conditions. 18 The results of the present study show that laryngeal stimulation during hypoxia (Pa02 of 50 to 65 mm Hg) results in a decrease in mean apnea duration and that a higher level of oxygénation before laryngeal stimulation results in a higher Pa02 level at the end of the apneic response. Despite this effect on apnea duration and recovery Pa02 level, hypoxia as defined in this study (mean prestimulation Pa02 level of 58.5 versus 82.5 mm Hg) did not affect the ability to recover from the apneic response without assistance.…”
Section: Discussionsupporting
confidence: 50%
“…In experimental animals this nucleus receives significant innervation from the 5-HT neurons of the caudal raphé, i.e., RPa, ROb, and to a lesser extent, RMg (Bago et al, 2002;Li et al, 1993;Manaker and Tischler, 1993), but does not contain any 5-HT neuronal cell bodies. Furthermore, HG motoneurons are stimulated by firing of the raphé 5-HT neurons (Fornal et al, 1996;Jacobs and Azmitia, 1992;Jacobs and Fornal, 1993;Veasey et al, 1995), and by 5-HT both in vitro (Arita and Ochiishi, 1991;Berger et al, 1992;Kubin et al, 1992) and in vivo, enhancing upper airway flow (Goding, 1998). The HG nucleus displays a progressive increase in volume, but not cell number, with increasing postnatal age in both humans (Nara et al, 1989) and experimental animals (Berger et al, 1992;O'Kusky, 1998).…”
Section: Significance Of Developmental Changes In 5-ht 1a Receptor Bimentioning
confidence: 99%
“…[1][2][3][4] In some animals, the response can last longer, resulting in severe hypoxia and potentially death. [14][15][16][17][18] The physiological determinants of response severity are still unknown. Specifically, it has been observed that two young animals that undergo laryngeal chemostimulation under seemingly similar physiologic conditions can have marked differences in response severity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been observed that two young animals that undergo laryngeal chemostimulation under seemingly similar physiologic conditions can have marked differences in response severity. 10,[14][15][16][17] Some animals may recover uneventfully, and others may have profound or fatal responses. When laryngeal stimulation is performed under hypoxic conditions, one of two responses has been observed: a shorter, more transient response or a more profound, fatal response.l'' It has been shown that when laryngeal stimulation is performed under normoxic conditions, resumption of respiration occurs when the PaC02 reaches a certain threshold.l'' In that study, severity of response, as defined by apnea duration, was associated with the Pa02 at the time respiration was resumed.…”
Section: Introductionmentioning
confidence: 99%